The Forward Rate and the Interest Parity - Stein, Jerome L. (Review of Economic Studies, 1965)
Journal Article The Forward Rate and the Interest Parity Get access Jerome L. Stein Jerome L. Stein Brown University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 2, April 1965, Pages 113–126, https://doi.org/10.2307/2296056 Published: 01 April 1965